Resources for the Family Caregiver: A Review of the Family Caregiver Alliance and the AARP Caregiving Resource Center. Issue 1 (2nd January 2019) - Phillips, Kat
Abstract: The rate of family caregiving is steadily increasing as baby boomers retire and their loved ones step into the role as family caregiver. Whether caregiving is a sudden or anticipated role, caregivers are often unsure of where to turn for information or aide, and face many challenges including stress, depression, anxiety, and financial burdens. Credible, easy, and useful online resources are abundant, and the Family Caregiver Alliance and the AARP Caregiving Resources Center are no exception. Each provide excellent starting points for caregivers new to the role, or seasoned caregivers seeking additional information. Other sources compliment these pivotal sites, but each can stand alone as a primary source for family caregiving information.